Seguimento por cinco anos de uma amostra de usuários de ecstasy (MDMA) - Battisti, Murilo Campos [UNIFESP] (2009)
Ecstasy (MDMA) is an important neurotoxic agent. Its use is described as a youth-limited phenomenon. The aims were to determine the natural course of ecstasy use within a five year timeframe in a sample of Brazilian young adults and to assess changes in ecstasy use patterns. Interviews took place in two waves: 2001 in São Paulo and in 2005/06. Data collection occurred through semi-structured interviews. The DSM-IV was used to assess ecstasy dependence. Qualitative method was utilized during the baseline sample (n=32) and the follow-up sample (n=21). All interviews were fully recorded, transcribed and interpreted though content analysis. Subjects’ average age was 24.8 years in the baseline group and 28.7 years in the follow-up. Three scenarios emerged: (A) the transient use group (n=14) either quit using ecstasy or cut down use significantly; (B) the long term habitual use (n=06) group maintained or cut down slightly on MDMA use; (C) the compulsive use group (n=01) increased ecstasy use by more than 50% over the course of the study. As ecstasy use shifts occurred, alcohol and marijuana consumption remained unaltered. Four respondents reported increases in cocaine use, and six subjects mentioned initiation in crystal methamphetamine use. For a group of respondents ecstasy use was a transient phenomenon. For another group of subjects MDMA use manifested as a lasting experience.